2008
DOI: 10.1097/mlg.0b013e3181559ff7
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Flap Reconstruction in Conjunction With Intraoperative Radiation Therapy for Advanced and Recurrent Head and Neck Cancer

Abstract: Reconstruction using flaps in the context of IORT can be achieved with expectation of good wound healing in the majority of cases despite heavy cumulative doses of radiation to recipient wound beds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
(45 reference statements)
0
8
0
1
Order By: Relevance
“…This technique replaces previously irradiated tissue with a healthy well‐vascularized radiation‐naive flap. Our group has published initial results with this technique 17. Wound healing was noted to be excellent in 76% of patients.…”
Section: Discussionmentioning
confidence: 93%
“…This technique replaces previously irradiated tissue with a healthy well‐vascularized radiation‐naive flap. Our group has published initial results with this technique 17. Wound healing was noted to be excellent in 76% of patients.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, Most et al [ 40 ] evaluated the feasibility of flap reconstruction, after submitting 21 patients (receiving 22 treatments) to IORT for advanced and recurrent head and neck cancer. Sixteen patients had SCC of the upper aerodigestive tract or cervical nodes, 2 had poorly differentiated parotid adenocarcinoma, 1 had high-grade parotid mucoepidermoid carcinoma, 1 patient had a recurrent synovial cell sarcoma of the parapharyngeal space, and 1 patient had an advanced cutaneous SCC of the nape of the neck.…”
Section: Resultsmentioning
confidence: 99%
“…The median IORT dose was 12.5 Gy. This study demonstrated that head and neck flap reconstruction can be performed in the setting of high cumulative doses of radiation with the expectation of good wound healing (28).…”
Section: Discussionmentioning
confidence: 96%